Budding of PPxY-Containing Rhabdoviruses Is Not Dependent on Host Proteins TGS101 and VPS4A - Irie, Takashi (American Society for Microbiology, 2004)
Viral matrix proteins of several enveloped RNA viruses play important roles in virus assembly and budding and are by themselves able to bud from the cell surface in the form of lipid-enveloped, virus-like particles (VLPs). Three motifs (PT/SAP, PPxY, and YxxL) have been identified as late budding domains (L-domains) responsible for efficient budding. L-domains can functionally interact with cellular proteins involved in vacuolar sorting (VPS4A and TSG101) and endocytic pathways (Nedd4), suggesting involvement of these pathways in virus budding. Ebola virus VP40 has overlapping PTAP and PPEY motifs, which can functionally interact with TSG101 and Nedd4, respectively. As for vesicular stomatitis virus (VSV), a PPPY motif within M protein can interact with Nedd4. In addition, M protein has a PSAP sequence downstream of the PPPY motif, but the function of PSAP in budding is not clear. In this study, we compared L-domain functions between Ebola virus and VSV by constructing a chimeric M protein (M40), in which the PPPY motif of VSV M is replaced by the L domains of VP40. The budding efficiency of M40 was 10-fold higher than that of wild-type (wt) M protein. Overexpression of a dominant negative mutant of VPS4A or depletion of cellular TSG101 reduced the budding of only M40-containing VLPs but not that of wt M VLPs or live VSV. These findings suggest that the PSAP motif of M protein is not critical for budding and that there are fundamental differences between PTAP-containing viruses (Ebola virus and human immunodeficiency virus type 1) and PPPY-containing viruses (VSV and rabies virus) regarding their dependence on specific host factors for efficient budding.